Mindful Tourism Services for People with Mental Impairment. Situation Scan: Latvia, 2021 - Van der Steina, Aija; Lūse, Agita; Rācene, Liene; Pazuhina, Nadežda; Popova, Diāna (Latvijas Universitātes Filozofijas un socioloģijas institūts, 2021)
The report is part of the EU Erasmus + funded project “Mindful tourism services for mentally disordered people” (MindTour). The project aims to promote and support tourism entrepreneurs to value mentally disordered clients and their families as persons and customers and help them design mindful tourism services accessible for mentally disordered people. The project is implemented in cooperation with Estonian, Belgian and Latvian higher education institutions – University of Tartu, Pärnu College (Estonia), Thomas More Mechelen-Antwerpen (Belgium), University of Latvia (Latvia), as well as leisure and tourism service providers - Pärnu Museum (Estonia), Museum Dr Guislain (Belgium) and SIA Zeit Hotel (Latvia). This report reveals the current situation in the use and accessibility of tourism services for people with mental impairment in Latvia. Researchers of the Institute of Philosophy and Sociology of the University of Latvia Agita Lūse, Liene Rācene, Diāna Popova, Nadezhda Pazuhina and Aija van der Steina researched in the autumn and spring semesters of the academic year 2020/2021, using both secondary data sources and gathering primary data through interviews with social service providers and tourism service providers, as well as participant observation and mapping of services, involving people with GRT in the consumption of tourism services.
Keywords: Mental impairment; tourism accessibility; social service; tourism services; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS